Gambaran Kadar Hemoglobin Sebagai Penanda Awal Anemia pada Santriwati Pondok Pesantren Darul Hijrah Puteri Martapura - Nurlaila Agustina; Hafiz Al Farizi; Yudi Yahya; Rizki Perdani (UPPM Politeknik Unggulan Kalimantan, 2024)
Anemia is a condition when the number of red blood cells or hemoglobin (Hb) levels in the blood is lower than the normal values ​​for the age group and gender. The decrease in hemoglobin levels is caused by poor diet, lack of iron intake through the food consumed, the amount of iron lost during menstruation, and knowledge of young women with anemia. This study aims to determine the description of hemoglobin levels as an early marker of anemia in female students at the Darul Hijrah Islamic Boarding School, Puteri Martapura. This type of research is qualitative descriptive research with a cross sectional design. The sampling technique used purposive sampling technique and the results obtained were 93 samples. From the results of this research, it was found that some female students experienced anemia, namely hemoglobin levels <12 g/dl. Based on these results, it can be concluded that 48 respondents (52%) experienced anemia, and 45 respondents (48%) did not experience anemia.